Paradidático como estratégia pedagógica para o ensino de química : aprendendo com uma planta chamada cana-de-açúcar - Fernandes, Karina Sasso (2019)
This study presents an investigation on the elaboration and evaluation of a sugar cane paradidátic book, which seeks to identify the possible contributions of the paradidátic, from the interpretative perspective of teachers and graduates in Chemistry. The research approach is based on the qualitative method, based on exploratory and documentary analysis techniques. Initially a survey was conducted on publications in the area of Chemistry Teaching, in the main events of recent years and journals in the area that contemplated the paradidátic and paradidátics terms. Secondly, in order to reach works that mention the theme Sugarcane, textbooks approved by PNLD / 2018 and some paradidátic books were analyzed. From this perspective, the paradidátic elaborated here seeks a possible union between contents close to the reality of the Mato Grosso students (the production of sugar cane and some of its chemical processes) to the approach Science, Technology and Society, which prioritizes the integral formation of the student. As for the theoretical assumptions, it uses the studies of Santos (2000, 2002, 2006, 2007, 2008, 2010), Mortimer (1988, 2000 e 2002), Schnetzler (2010), Linsingen (2007), Bazzo et al (2003), Garcia et al (1996) on the CTS approach, and Munakata (1997) and Dalcin (2002), being both Brazilian researchers and references on the subject of paradidátics. The paradidátic material QuimiCANA was elaborated, evaluated and will be published later. To evaluate the effectiveness of this teaching alternative, the research subjects answered a semi-structured evaluation questionnaire. After systematically analyzing the conclusions of the subjects about the paradidátic, we verify if it is considered according to the technical, pedagogical aspects and the CTS approach, as a valid and useful teaching instrument for both students and teachers working in basic education. from the state of Mato Grosso.